Building robust, practicable counterfactuals and scenarios to evaluate the impact of species conservation interventions using inferential approaches - Grace, MK; Akçakaya, HR; Bull, JW; Carrero, C; Davies, K; Hedges, S; Hoffmann, M; Long, B; Lughadha, EMN; Martin, GM; Pilkington, F; Rivers, MC; et al. (Elsevier, 2021)
Robust evaluation of the impact of biodiversity conservation actions is important not only for ensuring that conservation strategies are effective and maximise return on investment, but also to identify and celebrate successful conservation strategies. This evaluation can be retrospective (comparing the current situation to a counterfactual scenario) or forward-looking (comparing future scenarios with or without conservation). However, assessment of impact using experimental or quasi-experimental designs is typically difficult in conservation, so rigorous inferential approaches are required. Inferential assessment of impact is a key part of the new IUCN Green Status of Species, which greatly amplifies the need for standardised and practical species impact evaluation methods. Here, we use the Green Status of Species method as a base to review how inferential methods can be used to evaluate conservation impact at the species level. We identify three key components of the inferential impact evaluation process—estimation of scenario outcomes, selection of baseline scenario, and frame of reference—and explain, with examples, how to reduce the subjectivity of these steps. We propose a step-by-step guide, incorporating these principles, that can be used to infer scenario outcomes in order to evaluate past and future conservation impact in a wide range of situations, not just Green Status of Species assessments. We recommend that future non-experimental conservation interventions facilitate the process of evaluating impact by identifying the variable(s) that will be used to measure impact at the design stage, and by using conceptual models to help choose conservation actions most likely to have the desired impact.